Tinjauan Yuridis Tentang Pelaksanaan Simpan Pinjam Pada KPRI Makarya UPTD Dikpora Kecamatan Jebres - Margarany, Hanita Putri; , Inayah S.H., M.H (2017)
This study aims to determine the procedure and terms of implementation of the savings and loans, the problems and their solution then accountability board to the problems of savings and loan on KPRI Makarya. This research method using descriptive empirical jurisdiction. Sources of primary data, interviews and secondary data that is made from primary law and secondary law. Data were collected by interview and literature study then analyzed qualitatively. The results showed that the procedure and terms of implementation of the savings and loan on KPRI Makarya accordance with the Statutes of cooperatives and compliance according to the Law No. 25 of 1992 concerning Cooperatives. As for problems that arise and resolving disputes implementation of the savings and loans to KPRI Makarya is a member / borrowers prefer to repay its own loans and circulation of money on KPRI Makarya that are not in line with expectations, resulting in financial KPRI Makarya may be delayed, but because of the cooperative main activity is a savings and loan then the above problems can be overcome with good, while the board accountable to the problems arising from the implementation of KPRI Makarya store on board as a party which is empowered to manage the cooperative must be adhered to the principle of prudence in carrying out its authority.